Your critical first 10 days as a leader - McNulty, Eric J. (O'Reilly Media, 2015)
Get your leadership launch period right and you set yourself up for sustained, long-term success. Forget the first 100 days. As a leader, your impact begins from minute one. Within your first 10 days, your direct reports, boss, peers, and other key stakeholders will take your measure on how much they trust you, whether you inspire confidence, and how effectively you make decisions. These first days are so important because once an impression forms, the human brain prioritizes data that confirms the initial judgement. Early missteps are difficult to undo. In this book, you will find proven insights and practical techniques for making the most of your critical first 10 days. This book is your time-efficient, go-to guide for your new leadership role.